INNOVATIVE APPROACHES IN THE SYSTEM OF EDUCATIONAL ORGANIZATIONS AND THEIR IMPACT ON YOUTH UPBRINGING (Web of Teachers: Inderscience Research, 2026)
This article is devoted to an in-depth scientific, pedagogical, and sociological analysis of the impact of innovative approaches introduced in the system of educational and enlightenment organizations on the upbringing of youth, their spiritual and moral character, and social activity. The research reveals the necessity of transitioning from traditional upbringing methods to interactive, digital, and psychologically grounded new methods in modern educational institutions. In particular, innovative technologies such as gamification, intellectual tournaments, project-based learning, and the humanization of administrative relations are analyzed. The article details international and national experiences, including the practice of organizing the socio-cultural life of students in higher educational institutions, and develops scientifically based proposals for forming responsibility and values among the youth.